2018
DOI: 10.1038/s12276-018-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of the AAA-ATPase Ruvbl1 in mice disrupts ciliary integrity and causes renal disease and hydrocephalus

Abstract: Ciliopathies comprise a large number of hereditary human diseases and syndromes caused by mutations resulting in dysfunction of either primary or motile cilia. Both types of cilia share a similar architecture. While primary cilia are present on most cell types, expression of motile cilia is limited to specialized tissues utilizing ciliary motility. We characterized protein complexes of ciliopathy proteins and identified the conserved AAA-ATPase Ruvbl1 as a common novel component. Here, we demonstrate that Ruvb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 82 publications
1
23
0
Order By: Relevance
“…Although the levels of transcription in many components that build the dynein arms were unchanged [15,48], the transmission electron microscopy (TEM) analysis showed that, in both mutants, cilia had a reduced number of ODAs and IDAs [15]. Immunofluorescence analysis of mouse ependymal and oviduct epithelial multiciliated cells, as well as studies of Kupffer's vesicle and pronephric ciliated cells in zebrafish, showed that RuvBL1 was present in the cytoplasm [15,49] and in the nucleus [49]. Contradictory to these data, using a non-commercial antibody, it was shown that in Chlamydomonas RuvBL1 was also present in flagella [50].…”
Section: R2tp Complexes In the Dynein Arm Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…Although the levels of transcription in many components that build the dynein arms were unchanged [15,48], the transmission electron microscopy (TEM) analysis showed that, in both mutants, cilia had a reduced number of ODAs and IDAs [15]. Immunofluorescence analysis of mouse ependymal and oviduct epithelial multiciliated cells, as well as studies of Kupffer's vesicle and pronephric ciliated cells in zebrafish, showed that RuvBL1 was present in the cytoplasm [15,49] and in the nucleus [49]. Contradictory to these data, using a non-commercial antibody, it was shown that in Chlamydomonas RuvBL1 was also present in flagella [50].…”
Section: R2tp Complexes In the Dynein Arm Assemblymentioning
confidence: 99%
“…In transgenic RuvBL1 frt-fl mice disruption of ciliary integrity was observed, causing renal disease and hydrocephalus [49]. In mice, loss-of-function mutations of RuvBL1 is lethal at an early embryonic stage, but deletion of the RuvBL1 only in premeiotic male germ cells causes male infertility [15].…”
Section: R2tp Complexes In the Dynein Arm Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…6 Thus, ciliary dysfunction may differentially affect a variety of tissues including the brain, retina, heart, respiratory tract, skeleton, kidneys and urogenital tract. [7][8][9][10][11][12][13][14] As a consequence, dysfunction of different ciliarelated genes can cause remarkably different phenotypes across different tissues. Although several monogenic causes of ciliopathies have been identified, 15 different alleles of the same gene can also cause strikingly diverse disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Ruvbl proteins or protein complexes involving the Ruvbl proteins modulate transcriptional activity of, e.g., pro-proliferative factors like MYC and ß-catenin and play important roles in multiple steps of cell cycle progression and cellular metabolism [ 6 , 8 , 13 ]. We recently identified Ruvbl1 as a component of ciliary protein complexes in renal tubular, bronchial, and ependymal epithelial cells [ 15 ]. Ruvbl1 also seems to be essential for early embryogenesis in mice [ 15 , 16 ], and it has been suggested that loss of murine stem cell populations may be due to apoptosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%